455. Epidemiological Surveillance in Points of Care for Refugees/Migrants: The 2016–2017 Experience in Greece. (26th November 2018) - Gkolfinopoulou, Kassiani; Lytras, Theodore; Triantafyllou, Eleni; Mellou, Kassiani; Pervanidou, Danai; Kalkouni, Ourania; Lambrou, Angeliki; Chrysostomou, Anthi; Andreopoulou, Anastasia; Gouzelou, Stavroula; Katsaounos, Panagiotis; Baka, Agoritsa; et al.
Abstract: Background: In 2016 and 2017, 535, 000 refugees/migrants crossed the Mediterranean Sea to reach Europe, with 203, 000 arriving in Greece. To address enhanced epidemiological surveillance needs, in May 2016 Greece established an ad hoc surveillance system in points of care for refugees/migrants in hosting centers, complementary to routine surveillance. Methods: Data on number of cases per age group for 14 syndromes of public health (PH) interest were collected daily from primary healthcare units of refugee/migrant hosting centers in the country, along with the number of consultations from any cause. Additional information enabling case-finding was collected for syndromes representing diseases that require PH measures at an individual level. Observed daily proportional morbidity (PM) was compared with expected PM using a quasi-Poisson regression model. PM ≥2 standard deviations from expected was defined as a "warning signal." "Warning signals" appearing for ≥2 consecutive days were considered "alert signals." Signals were evaluated daily and public health measures were implemented as necessary. Results: The number of centers participating in the system ranged between 27 and 51. Mean weekly reporting rate reached 96%. From 16 May 2016 to 31 December 2017, 500, 166 consultations from any cause were reported, with 28, 300 cases of the syndromes under surveillance (5.6%). Syndromes with the higher PM were respiratory infections with fever (3.3%), gastroenteritis (1.3%), suspected scabies (0.6%), and rash with fever (0.3%, of whom 95.1% were varicella cases, with no measles or rubella identified). Two hundred fifteen cases of suspected tuberculosis were referred to hospitals for further diagnostic testing and treatment. Of 92 cases of jaundice with acute onset, 85% were verified as hepatitis A, triggering interventions such as vaccination. None of the produced signals corresponded to a major PH incident, all being of low severity and duration. Conclusion: Infections represented a small proportion of refugees' health problems. Syndromic surveillance in hosting centers guided PH action and confirmed no major PH event. Disclosures: All authors: No reported disclosures.